Optimizing ESG-Based TOD Implementation to Foster Inclusive and Sustainable Economic Growth - Muhammad Fadhil Athallah; Nefia Nur Fitri (Arthatama: Journal of Business Management and Accounting, 2025)
Transit-Oriented Development (TOD) serves as a tangible example of Environmental, Social, and Governance (ESG) implementation through integrated spatial planning approaches. This study explores the correlation between TOD and ESG principles in supporting inclusive and sustainable economic growth, particularly within the context of rapidly urbanizing cities in developing countries. Utilizing a Systematic Literature Review (SLR) method, the research examines various scholarly publications to assess both the potential and challenges of TOD aligned with ESG criteria. The findings indicate that ESG-based TOD can enhance land use efficiency, reduce environmental degradation, support social inclusion, and promote economic productivity. However, practical implementation often faces obstacles such as high investment requirements, the reduction of urban green spaces, and limited cross-sectoral coordination. In response to these challenges, this study proposes the Economic Environmental, Social, and Governance (EESG) framework to address the underrepresentation of economic dimensions in current ESG assessments. By integrating economic factors alongside environmental, social, and governance considerations, EESG-oriented TOD offers a comprehensive planning strategy to accelerate sustainable urban development in emerging economies.